The liquidity risk management guide : from policy to pitfalls - Adalsteinsson, Gudni, 1967- (Chichester, West Sussex, United Kingdom : Wiley, 2014)
"Liquidity risk is in the spotlight of both regulators and management teams across the banking industry. The European banking regulator has introduced and implemented a stronger liquidity regulatory framework and local regulators have made liquidity a top priority on their supervisory agenda. Banks have accordingly followed suit. Liquidity risk is now a topic widely discussed in boardrooms as banks strive to set up a strong and efficient liquidity risk management framework which, while maintaining sufficient resources, does not jeopardize the necessary profitability and return targets.The Liquidity Risk Management Guide: From Policy to Pitfalls is practical guide for banks and risk professionals to proactively manage liquidity risk in a systemic way. The book sets out its own comprehensive framework, which includes all the various and critical components of liquidity risk management. The recommendations are based on experiences from the recent financial crises, best practices and compliance with current and future regulatory requirements, with special emphasis on Basel III.Using the new 6 Step Framework, the book provides step-by-step guidance for the reader to build their liquidity management framework into a new overarching structure, which brings all the different parts of liquidity risk into one approach. Special attention is given to the challenges that banks currently face when adopting and implementing the Basel III liquidity requirements and guidance is given on how the new metrics can be integrated into the existing framework, providing the most value to the banks instead of being a regulatory reporting matter"--
Machine generated contents note: Preface 11 LIST OF FIGURES 1 Introduction 13 2 Primer in banking 21 3 The function - the framework on top of liquidity management 28 4 Liquidity - Background and Key Concepts 39 5 The appropriate Liquidity Framework - Introduction to the '6 Framework' 52 6 Step I: Sources of Liquidity Risks 60 7 Step II: Risk Appetite 90 8 Step III: Governance and High-Level Policy 104 9 Step IV: The Quantitative Framework 138 10 Step V: Stress Testing and the Contingency Funding Plan 153 11 Step VI: Reporting and Management Information 207 12 Basel III: The new global framework 212 Bibliography 229 Index .
Includes bibliographical references (pages 187-191) and index.
Keywords: Bank liquidity; Bank management; Risk management; Asset-liability management; BUSINESS & ECONOMICS / Finance